The Formation of Professional Ethical Qualities in Future Physical Education Teachers Poses a Pedagogical Challenge - Kholdorov Zokhid Abduvayitovich (International Journal on Integrated Education, 2024)
This work highlights the urgent need for substantial changes in the training content of prospective physical education teachers, emphasizing the integration of a module-rating system using information and communication technologies. The evolving landscape in our country, focusing on the integration of science and technology, presents a significant opportunity for the development of future specialists. The study underscores the global importance of enhancing professional training for physical education teachers, stressing the application of innovative education and addressing challenges in ethical training through modern pedagogical technologies.